2017
DOI: 10.1177/0093854817719103
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Context of Women Probationers and Parolees Who Engage in Violence

Abstract: For a sample of 396 women on probation and parole, this article presents the results of qualitative analysis that shows the nature of violence for a subgroup of 75 women who were convicted of a violent act. For the full sample of 396, the article also presents results of quantitative analyses that identify correlates of violent behavior. Women’s violent acts were most often assaults on people who were not intimate partners. Second and third most common violent acts were for assaults of an intimate partner and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 101 publications
(148 reference statements)
0
9
1
Order By: Relevance
“…A displayed a history of promiscuous behaviour that commenced at the age of 14 years, and she had multiple sexual partners. Research (Bui, 2018; CARE, 2004; Hopkins, 2016; Morash et al, 2017; Valabdass et al, 2021; Wise, 2017) argues that due to women’s disadvantaged social and economic backgrounds, women frequently engage in risky sexual behaviours for survival purposes. Carney et al (2019) and Nuytiens (2015) warn about promiscuous behaviour and possible engagement in criminality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A displayed a history of promiscuous behaviour that commenced at the age of 14 years, and she had multiple sexual partners. Research (Bui, 2018; CARE, 2004; Hopkins, 2016; Morash et al, 2017; Valabdass et al, 2021; Wise, 2017) argues that due to women’s disadvantaged social and economic backgrounds, women frequently engage in risky sexual behaviours for survival purposes. Carney et al (2019) and Nuytiens (2015) warn about promiscuous behaviour and possible engagement in criminality.…”
Section: Resultsmentioning
confidence: 99%
“…In turn, intimate relational vulnerability enhances feelings of insecurity and worthlessness and may lead to substance abuse and post-traumatic stress symptoms (Callaghan et al, 2018; Pelvin, 2019). This chain of events might ignite crimes such as murder (Callaghan et al, 2018; Morash et al, 2017; Nuytiens, 2015). Furthermore, relationships form a sound foundation for psychological health and disconnection, and isolation from significant others may become a breeding ground for psychological distress.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Pride in Delinquency Scale (PIDS; Shields & Whitehall, 1991) and the Measures of Criminal Attitudes and Associates (MCAA) measure (Mills et al, 2002) have shown to predict recidivism among justice-involved female youth (O’Hagan et al, 2019; Skilling & Sorge, 2014). However, in contrast, Morash et al (2018) observed that criminal attitudes as measured by the Women’s Risk/Needs Assessment (WRNA; Van Voorhis et al, 2008) did not predict women’s violence over a 2-year period using a sample of 396 women on probation and parole.…”
Section: Criminal Attitudes and Crimementioning
confidence: 99%
“…Likewise, Morash et al (2017) and Golder et al (2015) acknowledged the complex interplay between substance abuse, psychological distress, trauma, and violent victimization in the lives of CJS-involved women. Morash et al examined the violent experiences of 396 women on community supervision; described the troubling relationship between the history of abuse, anger, and mental illness; and suggested the need for programming to attend to the multilayered dimensions that explain engagement in female offenders supervised in the community.…”
Section: Barriers To Recoverymentioning
confidence: 99%